The Role of Fintech in Financial Inclusion: Analyzing 21st-Century Strategies, Innovations, and Challenges - Meilanta Rantina; Gatot Nazir Ahmad (Pattimura University, 2026)
This research discusses the role of financial technology (fintech) in enhancing financial inclusion in the digital era. Using a descriptive qualitative method, this research identifies the analysis, uniqueness, novelty, and strategies of fintech in expanding access to financial services for communities that have not yet been reached by the conventional banking system. The research results show that fintech has a positive impact on accelerating financial processes, increasing transaction efficiency, and providing alternative financing solutions for SMEs and individuals. However, there are challenges such as regulation, data security, and financial literacy that remain the main obstacles. The proposed solutions include strengthening government policies, enhancing digital literacy, and optimizing sustainable fintech business models. It seems there is no text provided for translation. The research findings reveal four main themes. First, fintech strategies have shifted from digital-only to a hybrid approach that combines digital platforms with networks of physical agents. Second, the biggest opportunities lie in leveraging data as a new asset and strategic partnerships using a B2B2C model. Third, disruptive innovation is not only in the product but in the entire user experience and the contextuality of services. Fourth, complex challenges include aspects of regulation that are not yet adaptive, the dual digital-financial literacy gap, and uneven infrastructure. Based on these findings, this research developed a Digital Financial Ecosystem Model that integrates these four aspects. The study concludes that optimizing the role of fintech requires a collaborative approach between fintech players, regulators, and the public to create an inclusive.